NEW FIND OF ZUNYITE IN ADVANCED ARGILLIC ALTERATION OF RHYOLITES, KOS ISLAND, SOUTH AEGEAN VOLCANIC ARC , GREECE - Papoulis, D.; Tsolis-Katagas, P.; Katagas, C. (Bulletin of the Geological Society of Greece, 2004)
Zunyite [Ali3SÌ5C>2o(OH,F)i8CI], an extremely rare mineral, was found as an accessory mineral in highly altered rhyolitic rocks at Kefalos, southwestern Kos, and in a completely kaolinized rhyolitic dyke at Asfendiou, northeastern Kos. It is associated with dickite, kaolinite, quartz and minor pyrophyllite. Kos Island contains both Tertiary and Quaternary volcanic rocks. Zunyite has been identified by XRD and studied by SEM, EDS, Raman spectroscopy and FTIR spectroscopy. The presence of zunyite, in the highly altered samples is significant for the determination of the conditions of the hydrothermal alteration that took place. Zunyite crystals, are up to 90 pm in diameter but usually are less than 10 pm; the crystals are partly covered by kaolinite layers. EDX analyses on the surface of zunyite revealed AI2O3/S1O2 values raging from 2.6 to 2.7. The occurrence of zunyite suggests incorporation of hydrothermal fluids rich in F" and CI", thus indicating contamination by seawater